DEVELOPMENT OF DEWATERIZATION OF BIO-CRUDE OIL (DBCO) PRODUCTION TECHNOLOGY BY VACUUM DISTILLATION - Dwi Oktavia, Fika
Thermochemical conversion, using a slow pyrolysis process, produces one of its products Fresh Bio-Crude Oil (FBCO). However, FBCO EFB has limitations as a fuel, primarily due to its moisture content, which significantly reduces its heating value. To overcome this issue, the water content is separated through a vacuum distillation process, producing light distillate and Dewaterization of Bio-Crude Oil (DBCO). Light distillate can serve as a food preservative in the food industry and as a biopesticide in the agricultural sector. On the other hand, DBCO shows promises as a renewable energy source and can be utilized to produce sustainable chemicals through the thermal cracking process. The best separation occurs at operating conditions of 95°C with a vacuum pressure of 30 kPa, resulting in a yield of light distillate 67.73% and DBCO 28.27%. The content of light distillate is mostly water 70.574%?98.805%, with small amounts of acetic acid 0.015%?0,284% and phenol 0.060%?0.091%. The resulting DBCO has the highest heating value, reaching 32.27 MJ/kg, mainly because it contains only a small amount of water, 4.91%. DBCO is composed of 8 classes of constituent compounds, including phenol and its derivatives 27.70%, acids and esters 28.86%, aromatics 7.56%, oxygenates 15.97%, alkanes 9.23%, alkenes 2.83%, furans 0.52% and alcohols 7.33% formed during the process. Large-scale DBCO production can be simulated using DSTWU (ideal conditions) and RadFrac (rigorous) columns. The FBCO feed enters with a 300 kg/hour flow rate under conditions of 25°C and 1 atm pressure. The simulation employs 21 stages with a reboiler heat load of 201.65 kW and a reflux ratio of 0.29. Calculations using Aspen Plus V10 result in light distillate with 94.57% and DBCO 10.14% water content. The distillation process operates at 82.24°C and vacuum pressure of 30 kPa.